KETERKAITAN COMPULSIVE GAMER DAN GANGGUAN PADA SISTEM LIMBIK OTAK DALAM PEMBELAJARAN KEAGAMAAN ISLAM - Istiqomah Istiqomah; Suyadi Suyadi (Universitas Muhammadiyah Ponorogo, 2019)
This article aims to examine the compulsive domain, the positive and negative effects of playing games, the brain structure of both neuroanatomy and physiology that gets influence or disturbance in playing games to problematic levels, and sees it in an Islamic perspective. This study is a literature review with a descriptive qualitative approach. Data analysis techniques are carried out by clarifying, comparing and interpreting themes related to compulsive games, game addiction, neurology especially the limbic system, the positive impact of playing games, the impact of addictive games and the study of Islamic and educational perspectives. The results of this study indicate that compulsive games are one indicator of game addiction. Parts of the brain that experience even the most disturbed effects are experienced by the limbic system. There are positive and negative effects in playing games. Addictive games are also synonymous with a person's condition in a real life escape that underlies the occurrence of disorders such as fear, stress, depression, and other negative emotions. In the Islamic view, playing games is interpreted as a game in general. This becomes prohibited when it comes to using all opportunities, time and ultimately neglecting obligations. This is where the role of parents / family in education becomes absolute in organizing children's behavior so that it does not reach the realm of compulsive games.